2013
DOI: 10.4317/medoral.18746
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal features in patient affected by maxillary canine impaction

Abstract: Objective: To analyze the skeletal features of patients with maxillary canine impaction. Material and Methods: The complete pre-treatment records of 1674 orthodontic patients were examined. From the subjects with maxillary impacted canine 12 patients were excluded , remaining 108. The subjects with maxillary impacted canine were divided into two study groups: a palatally displaced canine group (PDCG) (77 patients) and a buccally displaced canine group (BDCG) (31 patients). The values of the skeletal features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 26 publications
2
25
2
9
Order By: Relevance
“…Palatally displaced canines have been associated with missing lateral incisors and other animalies [19][20][21][22] . In another study, palatally displaced canines were reported to be associated with peg-shaped or missing lateral incisors, other impacted and missing teeth and deep bite with retroclined maxillary incisors 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Palatally displaced canines have been associated with missing lateral incisors and other animalies [19][20][21][22] . In another study, palatally displaced canines were reported to be associated with peg-shaped or missing lateral incisors, other impacted and missing teeth and deep bite with retroclined maxillary incisors 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the radiographic criteria developed by Ericson and Kurol (5) and further modified by other authors (6,7) to predict canine impaction from its position in a panoramic radiograph, some authors have studied if a patient’s dento-skeletal features could be used as a prognostic factor. For example, Mercuri et al found that the facial skeletal features of patients with a palatally impacted canine are characterized by a horizontal and prognathic growth (8). Larsen et al observed that the maxillary complex of patients with ectopic canines is enlarged transversally, but smaller in the sagittal and vertical dimensions (9).…”
Section: Introductionmentioning
confidence: 99%
“…29 Moreover, some authors studied other factors that could be used to predict the risk of canine impaction, such as skeletal features. 20 Mercuri et al, 18 reported that patients with impacted canines were characterised by a horizontal and prognathic growth and Larsen et al, 19 found that the dimension of the maxilla in subjects with palatally displaced canines was reduced vertically and sagittally, but increased transversally.…”
Section: Discussionmentioning
confidence: 99%